2001
DOI: 10.1097/00000374-200105051-00005
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Acetaldehyde in the Actions of Alcohol (Update 2000)

Abstract: AcH plays a role in most of the actions of alcohol. The individual variability in these AcH-mediated actions will depend on the genetic polymorphism, not only for the alcohol and AcH-metabolizing enzymes but also for the target sites for AcH actions. The subtle balance between aversive and reinforcing, protecting and promoting factors will determine the overall behavioral and pathological developments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(108 citation statements)
references
References 269 publications
(180 reference statements)
3
103
1
1
Order By: Relevance
“…A substantial number of Asians (50-80 per cent), compared with Caucasians (3-12 per cent), exhibit flushing [39,40]. Acetaldehyde creates unpleasant adverse reactions by acting as a major deterrent to excessive alcohol drinking on the one hand, while giving the euphoric sensations that may reinforce alcohol drinking on the other [41]. …”
Section: Discussionmentioning
confidence: 99%
“…A substantial number of Asians (50-80 per cent), compared with Caucasians (3-12 per cent), exhibit flushing [39,40]. Acetaldehyde creates unpleasant adverse reactions by acting as a major deterrent to excessive alcohol drinking on the one hand, while giving the euphoric sensations that may reinforce alcohol drinking on the other [41]. …”
Section: Discussionmentioning
confidence: 99%
“…This may be co-morbid with viral infection (Chen et al, 1991;Shen et al, 1996), nutritional deficiencies (French, 1993;Lieber, 2001), or related to formation of free radicals (Bautista & Spitzer, 1992). Moreover, acetaldehyde, the major metabolite of alcohol, is thought to play a significant role in the pathogenesis of alcohol liver disease (Eriksson, 2001). It has recently been suspected that alcohol dehydrogenase may be a susceptibility gene to both alcoholism and alcohol-related organ damage including liver disease (Yin & Agarwal, 2001).…”
Section: Organ Damage and Alcohol-metabolizing Enzyme Genesmentioning
confidence: 99%
“…Acetaldehyde, the major metabolite of alcohol, was thought to play a significant role in the pathogenesis of alcohol liver disease (Eriksson, 2001). However, it was recently reported that genotypes of alcohol dehydrogenase (ADH) and aldehyde dehydrogenase are not associated with risk of mortality from liver diseases (Chen et al, 2004).…”
mentioning
confidence: 99%